Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Keputusan Pembelian Konsumen pada PT. Karsa Utama Lestari Gorontalo - Peris Igirisa; Radia Hafid; Agil Bahsoan; Umin Kango; Rierind Koniyo (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the extent to which the role of product and service quality in influencing consumer decisions to make purchases at Karsa Utama. This study applies a quantitative approach with data collection techniques through surveys. Data processing was conducted using multiple linear regression analysis with the help of statistical software. The results of the analysis show that both product quality and service quality have a significant effect on consumer purchasing decisions. Partially, product quality has an effect of 39.6% and service quality of 26.3%. Simultaneously, the two independent variables contributed 65.9% to consumer purchasing decisions, while 34.1% was influenced by other factors outside this study. This finding indicates that improving product and service quality can directly encourage consumers' tendency to make purchasing decisions.